Relative entropic uncertainty relation for scalar quantum fields - Flörchinger, Stefan; Haas, Tobias; Schröfl, Markus (SciPost physics, 2022)
SciPost Journals Publication Detail SciPost Phys. 12, 089 (2022) Relative entropic uncertainty relation for scalar quantum fields
Gesehen am 31.05.2022